Tetra-N-silylated Bis(borylene)tetraaminoperylenes (“DIBOTAPs”): synthesis, structures and photophysics - Martens-Kruck, Susanne; Riehm, Till; Wadepohl, Hubert; Gade, Lutz H. (European journal of inorganic chemistry, 2012)
Silylated N,N′;N″,N″′-diborylene-3,4,9,10-tetraaminoperylenes (DIBOTAPs, compounds 1-4) were synthesized by treating 4,9-diaminoperylenequinone-3,10-diimine (DPDI, 1 equiv.) with BH3-THF (2 equiv.), lithiation with n-butyllithium (4 equiv.), and subsequent addition of the corresponding silyl chloride (4 equiv.). The structures of all compounds were determined by single-crystal X-ray diffraction analysis. In all cases, the perylene backbones are not completely planar. In general, local deviations from planarity are smallest within the central C6 ring [root-mean-square deviations (rmsd) range from 0.002 Å for 4 to 0.027 Å for 2·C6D6] and largest within the C3N2B rings [rmsd range from 0.05 Å for 4 to 0.096 Å for 2·C6D6]. The emission spectra of the DIBOTAP derivatives 1-4 in hexane as well as in THF are mirror images of the absorption spectra with Stokes shifts of about 10 nm. By variation of the steric demand of the silyl groups, the luminescence quantum yields could be further influenced. The exchange of all three methyl groups with ethyl (compound 1) or isopropyl (compound 2) substituents resulted in a significant increase in quantum yields with values of 92 % and 89 %, respectively. The observed fluorescence decay is monoexponential for all dyes with typical lifetimes of 5.5-6.6 ns.
First published: 08 May 2012
Gesehen am 10.10.2018